2020
DOI: 10.3390/nu12020284
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge about the Effect of Nutritional Status, Supplemented Nutrition Diet, and Gut Microbiota on Hepatic Ischemia-Reperfusion and Regeneration in Liver Surgery

Abstract: Ischemia-reperfusion (I/R) injury is an unresolved problem in liver resection and transplantation. The preexisting nutritional status related to the gut microbial profile might contribute to primary non-function after surgery. Clinical studies evaluating artificial nutrition in liver resection are limited. The optimal nutritional regimen to support regeneration has not yet been exactly defined. However, overnutrition and specific diet factors are crucial for the nonalcoholic or nonalcoholic steatohepatitis liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 176 publications
(234 reference statements)
3
50
0
Order By: Relevance
“…While many studies have focused on the impact of adding nutrients into a system on associated gut microbiome structure, a literature review revealed only limited investigations of bacterial community shifts during host starvation ( Xia et al, 2014 ; Davis, 2016 ; Seitz et al, 2019 ; Cornide-Petronio et al, 2020 ; Golonka et al, 2020 ; Jing et al, 2020 ; Schroder et al, 2020 ). In fact, little is known about the impact of fasting on the microbiome of invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have focused on the impact of adding nutrients into a system on associated gut microbiome structure, a literature review revealed only limited investigations of bacterial community shifts during host starvation ( Xia et al, 2014 ; Davis, 2016 ; Seitz et al, 2019 ; Cornide-Petronio et al, 2020 ; Golonka et al, 2020 ; Jing et al, 2020 ; Schroder et al, 2020 ). In fact, little is known about the impact of fasting on the microbiome of invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have confirmed that malnutrition dramatically increase the occurrence of postoperative complications in cancer patients, negatively affects the anticancer efficacy, length of hospital stay and quality of life of cancer patients, and also speeds up the progress of cancer, leading to poor survival (11)(12)(13)(14). Since nutritional status may be an important factor affecting the degree of liver regeneration, and preoperative malnutrition is highly correlated with the incidence of postoperative liver failure and postoperative death, this phenomenon is particularly evident in the field of liver surgery (15)(16)(17). Based on the above findings, several nutrition-based scores have been identified in recent years as possible prognostic markers for various cancers, and the details of these scores are readily available from peripheral blood samples (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…This method of effectiveness is controversial and rarely examined [ 141 , 142 , 143 ]. It is important to note that nutritional status, diet, presence of steatosis or other hepatic alterations influence the effects of conditioning maneuvers and their outcome [ 144 , 145 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%